Pandemic leadership: Lessons from New Zealand's approach to COVID-19. - Wilson S (Australia New Zealand School of Government for the John L. Alford Case Library, 2021)
The emergence of the novel coronavirus in late 2019 and its’ subsequent global spread created two core challenges for leaders in the public sphere, be they politicians or public servants. Firstly, both elected and appointed leaders needed to make decisions about how to tackle the virus under conditions marked by urgency, uncertainty, complexity and with high stakes impacts. Secondly, efforts to limit the spread of the virus involved a heavy reliance on securing voluntary compliance from the community at large, thus necessitating effective communication by both elected and appointed leaders to secure that buy-in. This case study examines the leadership approach to COVID-19 adopted by New Zealand’s Prime Minister Jacinda Ardern, focussed on the first wave of the outbreak in early 2020. That approach was characterized by science-led and timely decision-making, underpinned by strategic clarity about the nature of the challenges being faced and a focus on protecting lives and livelihoods as key guiding principles. Ardern’s communication mobilized collective effort which, along with government initiatives designed to cushion the pandemic’s impact on individuals and businesses, helped secure the compliance needed to halt community-based transmission of COVID-19. The case gives students the opportunity to explore leadership challenges related to decision-making and communication under volatile, complex and uncertain conditions where high stakes risks and impacts exist and where securing voluntary compliance is critical to ensuring decisions can be successfully implemented, meaning effective leader communication is vital. While Ardern is an elected leader, the leadership practices highlighted in the case nonetheless offer transferable lessons in respect of decision making and communication for appointed public service leaders also.
Keywords: COVID-19; crisis leadership; decision-making; Jacinda Ardern; leader communication; New Zealand; voluntary compliance